ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN TAPANULI UTARA - Sianturi, Yulinda Gita Angely; Silalahi, Evelin Roma Riauli (Jurnal Ilmiah Akuntansi (JIMAT), 2024)
This research aims to find out how much effectiveness and contribution to rural and urban land and building tax revenue in Tapanuli Utara Regency. The population in this study is target data and realization of rural and urban land and building tax revenues in the Tapanuli Utara Regency Regional Revenue Agency from 2009 to 2022. The sample in this study is the target and realization of rural and urban land and building tax revenues in 2018- 2022. The research method used is descriptive analysis with formulas for level of effectiveness and level of contribution. The results of this research, it shows that the level of to rural and urban land and building tax revenue effectiveness in 2018-2022 has an average of 89.24%. With the "quite effective" category. And the to rural and urban land and building tax revenue contribution to local own-source revenue for 2018-2022 has an average of 2.20% and is classified as "very low". And the level of rural and urban land and building tax contribution to local own-source revenue in 2013-2017 has an average of 1.92%. In the "very poor" category. The level of contribution of rural and urban land and building tax revenue to local own-source revenue during the 5 years of research, namely 2018-2022, has increased from the 5 years before the research, namely 2013-2022.